Double-brooding in Southern Yellow-billed Hornbills Tockus leucomelas. (8th June 2021) - Stanback, Mark; Millican, David; Versfeld, William; Nghikembua, Matti; Marker, Laurie; Mendelsohn, John
Abstract : Double-brooding is an avian breeding strategy where birds produce at least two successful nests in a single season. Double-brooding is seen most frequently in small passerines for which the breeding season is lengthy enough that they can easily fit in multiple nesting attempts. Such a pattern of breeding is therefore less common among large birds with long incubation periods and slow offspring development. In the case of hornbills (Family Bucerotidae), double-brooding would be unexpected for not only these reasons, but also due to the fact that the females of nearly all hornbill species exhibit a synchronous moult of flight feathers immediately following clutch completion. Double-brooding would thus require not only an exceptionally long breeding season, but also that females undergo two very costly flight feather moults in a single season. Here we describe the double-brooding of 10 individual female Southern Yellow-billed Hornbills Tockus leucomelas in a single Namibian population during the 2019/2020 breeding season. Because the breeding cycle of Yellow-billed Hornbills lasts three months, double-brooding requires that conditions remain appropriate for breeding for more than half the year, a stringent requirement in a relatively arid country. Our analysis demonstrates that double-brooding is not a response to either small spring brood sizes or the disappearance of fledglings and appears not to be limited to females of above-average mass. Rather, we found that double-brooding is most common among females who initiated their spring nest early and appears to be associated with wetter-than-average years.